Posterior Ligament–Bone Injury Classification and Severity Score: A Novel Approach to Predict the Failure of Anterior-only Surgery for Subaxial Cervical Facet Dislocations. Issue 4 (15th February 2021) - Yang, Jun-Song; Liu, Peng; Liu, Tuan-Jiang; Zhang, Hai-Ping; Zhang, Zheng-Ping; Yan, Liang; Zhao, Qin-Peng; He, Bao-Rong; Tuo, Yuan; Zhao, Yuan-Ting; Huang, Da-Geng; Hao, Ding-Jun
Abstract : Study Design: Clinical case series. Objective: The aim of this study was to propose a novel posterior ligament-bone injury classification and severity (PLICS) score system that can be used to reflect the severity of subaxial cervical fracture dislocations (SCFDs) and predict the failure of anterior-only surgery; and to measure the intraobserver and interobserver reliability of this system. Summary of Background Data: The approach selection for SCFDs is controversial. Although the anterior approach is familiar for most surgeons, postoperative hardware failure and/or delayed cervical deformity is a nonnegligible complication. Methods: Ten patients were randomly selected for intraobserver reliability evaluation on two separate occasions, one month apart. Another 30 patients were randomly selected, and the interobserver reliability was measured by comparing results of each case between each reviewer and averaging. To analyze the difference in the PLICS score, 354 patients fulfilled the follow-up were divided into stable and unstable groups according to whether radiologically stable was observed during follow-up. Results: For the intraobserver reliability, the mean intraclass correlation coefficient for the 10 reviewers was 0.931. For the interobserver reliability, the mean interobserver correlation coefficient for the three elements was 0.863. Among 16 patients with PLICS score ≥7, two patients in the stable group manifested with severe injury of the posterior ligamentous complex (PLC); extremely unstable lateral mass fractures with or without severe injury of PLC were detected in the 14 patients of the unstable group. Conclusion: The proposed PLICS score system showed excellent intraobserver and interobserver reliability. When a PLICS score is >7 or 7 accompanied by extremely unstable lateral mass fractures, the risk of postoperative failure after an anterior-only reconstruction is high and supplemental posterior strengthening can be considered. Level of Evidence: 4 Abstract : We introduced a novel classification and scoring system called the posterior ligament-bone injury classification and severity score into the treatment of subaxial cervical fracture dislocations, which is with excellent intraobserver and interobserver reliability and valuable to predict the risk of implant failure after a single anterior approach.